Globe avulsion secondary to maxillofacial trauma - Abdul Rahman, Norazah; Akmal, H.Z.; Hashima, H.; Vasantha, T.; Samsudin, Amir (Malaysian Medical Association, 2011)
SUMMARY: We report a case of globe avulsion secondary to maxillofacial trauma and propose potential mechanisms of injury. This case highlights the importance of wearing proper safety attire, especially during motorcycling.